12. Peran ASEANAPOL dalam Pemberantasan Peredaran Narkoba di Indonesia - Apriliantin Putri Pamungkas; Reni Windiani; Nadia Farabi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Between 2010 – 2014, the region of Southeast Asia had witnessed the increasing cases of transnational crimes relating to drug trafficking, especially in Indonesia. Therefore, the member states of ASEAN create regional cooperation to overcome said crime in this area. This research aimed to describe the regional cooperation of ASEANAPOL particularly on the role and effort made by the organization to the practice of drug crimes occured in Indonesia. By using descriptive and qualitative method, this research incorporates the framework of international cooperation theory, libreralism institutionalist, and liberalism interdependence to observe the works of ASEANAPOL in dealing with Indonesian drug cases. Set against data from several sources, this research concludes that the role of ASEANAPOL is to facilitate ASEAN regional cooperation and to organize formal and informal meeting among the member states’ law enforcement institutions. Although there are some obstacles to overcome drug crimes in Indonesia, sufficient to say that the number of Indonesian drug cases has decreased following the coordination and cooperation of ASEANAPOL.